University Students with Dyslexia: A Qualitative Exploratory Study of Learning Practices, Challenges and Strategies. (28th November 2016) - MacCullagh, Lois; Bosanquet, Agnes; Badcock, Nicholas A.
Abstract : People with dyslexia are vastly under‐represented in universities (Katusic et al., 2001, Richardson & Wydell, 2003 ; Stampoltzis & Polychronopoulou, 2008 ). This situation is of concern for modern societies that value social justice. This study was designed to explore learning experiences of university students with dyslexia and factors that could contribute to their success. Thirteen students with dyslexia and 20 non‐dyslexic peers were interviewed about their university learning experiences using a semi‐structured qualitative approach. Students with dyslexia described engaging in learning activities intensively, frequently and strategically. They reported challenges and strengths relating to study skills, lectures, assessments, technology and support services. They also described helpful strategies including self‐directed adaptive techniques, provisions from lecturers and assistance from the university. These findings suggest that students with dyslexia experience broad challenges at university, but helpful strategies may be available. Copyright © 2016 John Wiley & Sons, Ltd.